IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT: THE EFFECT ON PATIENT SAFETY CULTURE, SERVICE QUALITY, AND ITS IMPACT ON PATIENT SATISFACTION AND PRIVATE HOSPITAL PERFORMANCE IN MANADO CITY - Pondaag, Jessy Jousina; Kindangen, Paulus; Tawas, Hendra N.; Sumarauw, Jacky Sigfried Beatrix (Archives of Business Research, 2021)
The purpose of this research is to determine the effect of implementation of Total Quality Management (TQM) on patient safety culture, service quality, patient satisfaction, and hospital performance. This research conducted in private hospitals in Manado City which are: GMIM Pancaran Kasih Hospital, Advent Hospital, Sitti Maryam Hospital, and Siloam Hospital. The research approach used in this research is quantitative approach. The population in this research is the inpatients. Data collection technique conducted by questionnaires, documentation and observation. The sampling technique used in this research is saturated sampling (census). Data analysis conducted by using path analysis with the using SPSS ver. 25. The result of this research shows that the implementation of Total Quality Management impacted positively significantly on patient safety culture, the implementation of Total Quality Management impacted positively significantly on hospital service quality, the implementation of Total Quality Management impacted insignificantly on patient satisfaction, the implementation of Total Quality Management impacted positively significantly on hospital performance, Patient Safety Culture impacted positively significantly on patient satisfaction, Patient Safety Culture impacted positively significantly on hospital performance, Service Quality impacted positively significantly on hospital performance, Hospital Performance impacted positively significantly on hospital performance, and Patient Satisfaction impacted positively significantly on hospital performance.